Measuring Rationality and Cognitive Debiasing - Makay, Mátyás (Magyar Rendészet, 2017)
Measuring intelligence has a century old tradition but rationality is perhaps an even more important cognitive ability of efficient thinking. The paper explains the concept of RQ (Rationality Quotient), the cognitive biases that saturate our rational thinking and also the possible methods of cognitive debiasing. This subject has a crucial importance when one works in a field or position where decisions carry larger than average importance and where unusually high risks and uncertainty prevail.